Slovensko raziskovanje trivialne literature po letu 1980 - Pregelj, Barbara (Jezik in slovstvo, 1998)
The author reviews research of trivial literature in Slovenia, which has been since 1980 receiving considerable attention, especially in genological studies of traditionally genres. Discussins on trivial literature change dramatically in the context of production and research of postmodernist literature, where previoisly valid axiological dichtomies were surpassed.
Keywords: Slovene literature; slovenska književnost; history of literature; literarna zgodovina; trivialna književnost; literary theory; literarna teorija